EFFECT OF SHOULDER REHABILITATION PROTOCOL ON QUALITY OF UPPER LIMB FUNCTION FOLLOWING MODIFIED RADICAL MASTECTOMY - Shaikh, Amrin Ahmed; G. Varadharajulu, (International Journal of Psychosocial Rehabilitation, 2020)
This study was undertaken with the aim to determine the Effect of Shoulder Rehabilitation Protocol on quality of upper limb function following modified radical mastectomy. The basic objective of this study was to study the quality of function of the affected upper extremity. This study was done in Krishna Hospital, Karadand Mahathma Gandhi Cancer Hospital, Miraj.28 patients who had undergone modified radical mastectomywith age group between 35-65years divided into two groups, 14 females in each group. A thorough assessment was performed and outcome was seen with Range of Motion, Visual Analog Scale and Upper Extremity Functional Index.Group Awas treated with Shoulder Rehabilitation Protocol for 8 weeks, Group B was not treated. The score for Visual Analog scale ,Upper extremity functional index and Shoulder Range of motionwere taken on Day1, Day5, Day10, 1month and 2months respectively.Statistical analysis was done by using Instat software in which Friedman test with post-test were used to analyze scores of Visual Analog scale and Upper Extremity Functional Index .Repeated Measures ANOVA with post-test were used to analyze score of Shoulder Range Of Motion .Statistical analysis revealed that there was extremely significant difference between values of Group A and Group B(P